miRNA-218 Targets Lipin-1 and Glucose Transporter Type 4 Genes in 3T3-L1 Cells Treated With Lopinavir/Ritonavir - Bresciani, Elena; Saletti, Cecilia; Squillace, Nicola; Rizzi, Laura; Molteni, Laura; Meanti, Ramona; Omeljaniuk, Robert J.; Biagini, Giuseppe; Gori, Andrea; Locatelli, Vittorio; Torsello, Antonio (Frontiers in Pharmacology, 2019)
Background: Metabolic complications represent a common and serious problem associated with HIV infection and combined Antiretroviral Therapy (cART). Alterations in body fat distribution are associated with significantly increased risks of (i) metabolic derangements, (ii) cardiovascular pathologies, and (iii) insulin resistance. A case control study showed that in subcutaneous adipose tissue from HIV-infected patients on cART presenting lipodystrophy (LS), the levels of miRNA-218 were upregulated and those of lipin-1, a putative target gene of miRNA-218, were downregulated compared with HIV-negative subjects. Lipin-1 is one of the most important factors linked to development of LS. Lipin-1, by controlling PPARγ2, regulates the expression of specific genes, such as that of Glucose Transporter Type 4 (GLUT-4), required for maturation and maintenance of adipocytes. Objectives: To determine whether lopinavir/ritonavir (LPV/RTV) can modulate lipogenesis in adipocytes affecting miRNA-218 and lipin-1 mRNA expression, and to investigate the functional link between miRNA-218 and GLUT-4 mRNA expression. Methods: Differentiated 3T3-L1 cells were treated with various combinations of LPV/RTV, followed by measurements of cell viability, lipid accumulation, lipin-1 and GLUT-4 mRNA and miRNA-218 levels. Transfection of anti-miR-218 or a miRNA-218 mimic were used to investigate the role of miRNA-218 in lipogenesis. Results: LPV/RTV treatment of 3T3-L1 cells did not affect the viability of differentiated 3T3-L1 cells, but caused (i) a significant decrease of lipid accumulation, (ii) an overexpression of miRNA-218, and (iii) a reduction of lipin-1 and GLUT-4 mRNA levels. The anti-miR-218 transfection of 3T3-L1 cells significantly ameliorated the adipogenic dysfunction and restored mRNA levels of lipin-1 and GLUT-4 consequent to LPV/RTV treatment. By contrast, 3T3-L1 cells transfected with a specific miRNA-218 mimic showed (i) an overexpression of miRNA-218, (ii) a reduced cellular lipid fraction, and (iii) decreased levels of mRNA for lipin-1 and GLUT-4. Conclusions: 3T3-L1 cells, treated with LPV/RTV, show altered lipid content due to increased miRNA-218 levels, which affects lipin-1 mRNA. Moreover, increased miRNA-218 levels were inversely correlated with changes in GLUT-4 expression, which suggests a role for miRNA-218 in mediating the insulin resistance consequent to cART.